Strategies for sustainable natural resource management - Place, Frank; Reij, Chris; Tembo, Gelson; Franzel, Steven (International Food Policy Research Institute, 2004)
This brief describes two case studies as follows: "Sub-Saharan Africa, with the highest fertility rate in the world, faces increasing demographic pressure on its natural resource base.... Old strategies for coping with these new pressures on the natural resource base are becoming increasingly infeasible... Consequently, Africa's farmers require new solutions to address the increasing pressure on the continent's soil and water resources. Among hundreds of innovative efforts across the continent, two promising sets of responses have emerged in different locations.... First is the use of planting basins, an approach that has emerged in recent decades in both the Sahel and Zambia.... The second strategy involves the use of improved fallows, introduced over the past decade in eastern Zambia and western Kenya." [from Text]. The authors look at the impact and the drivers of change and conclude with key lessons learned for buidling future successes.